Waste Analysis In Delivery Process Using The Lean Distribution Method - Adhella Ika Putri; Ernawati, Dira (AI Society & STMIK Indonesia, 2024)
In the current era of globalization, the existence of goods delivery service companies supports almost every area of human life. In the process of delivering goods, PT. X always strives to provide fast and precise service. However, the problem faced by the company is the long lead time for delivery of goods. This study employs a lean distribution approach, applying Value Stream Mapping and identifying waste using the 8 waste framework. The research findings revealed waiting recapitulation of 20%, excess processing of 18%, overproduction of 17%, defects of 13%, non-utilized talent of 10%, inventory of 9%, transportation of 7%, and motion of 6%. With proposed improvements, the delivery process time can be reduced from 8243 minutes to 5929 minutes.